Breastfeeding Education for Third Trimester Pregnant as an Effort for the Success of Exclusive Breastfeeding - Nuryati, Elmi; Hashim, Faridah; Ponnampalam, Paramjothi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Good and effective health education will help families to create a healthy and intelligent generation. One of them is education about exclusive breastfeeding because breast milk is the basis or foundation of life and the best food for babies. This study aimed to determine the effect of breastfeeding education on pregnant women in the third trimester with the practice of exclusive breastfeeding in the Pringsewu Regency. The type of comparative analytic research with the research design used is quasi-experimental. The sample consisted of 126 respondents from 9 sub-districts in the Pringsewu district with the criteria for pregnant women in the third trimester, primipara and multipara, living in rural areas. The Source of data is primary data that was observed for six months postpartum mothers. Analysis of the data used is the t-test. The results showed that mothers who could breastfeed exclusively were 88.1%. There is a relationship between breastfeeding education in third-trimester pregnant women and the practice of exclusive breastfeeding with a p-value of 0.001 (less than 0.05). This finding means that preparing mothers in the third trimester of pregnancy through breastfeeding education is very effective for successful breastfeeding. In this case, midwives and health professional is very important to provide education during pregnancy check-ups.  Abstrak: Pendidikan kesehatan yang baik dan efektif akan membantu keluarga untuk menciptakan generasi yang sehat dan cerdas. Salah satunya adalah pendidikan tentang ASI ekslusive, karena ASI merupakan dasar atau pondasi kehidupan dan makanan terbaik bagi bayi. Tujuan penelitian ini adalah untuk mengetahui pengaruh pendidikan menyusui pada ibu hamil trimester III dengan praktik pemberian ASI eksklusif di Kabupaten Pringsewu. Jenis penelitian analitik komparatif dengan desain penelitian yang digunakan adalah quasy eksperimen. Sampel berjumlah 126 responden yang berasal dari 9 kecamatan di kabupaten Pringsewu dengan kriteria ibu hamil trimester 3, primi dan multipara, tinggal di daerah pedesaan. Sumber data adalah data primer yang di observasi selama 6 bulan ibu post partum. Analisis data yang digunakan adalah uji t test. Hasil penelitian menunjukkan ibu yang mampu memberikan asi secara ekslusive sebesar 88,1%. Ada pengaruh pendidikan menyusui pada ibu hamil trimester 3 dengan praktik pemberian asi ekslusive dengan nilai p value 0,001 (kurang dari 0,05). Temuan ini bermakna bahwa mempersiapkan ibu pada kehamilan trimester 3 melalui pendidikan menyusui sangat efektif untuk keberhasilan menyusui. Dalam hal ini peran bidan dan tenaga kesehatan lainnya sangat penting untuk memberikan edukasi saat pemeriksaan kehamilan.